Determining the Impacts of Oil Pollution and a Sustainability Assessment in Nigeria - Ben, Ime; Nwankpa, Chigozie; Baird, Jim (Current Advances in Geography, Environment and Earth Sciences Vol. 3, 2022)
The increasing impact of climate change has spurred public interest in identifying the long-term consequences of people's actions. While environmentalists continue to push for accountability, the majority of people in the areas where the majority of these pollutions occur, particularly in oil-producing regions, have no say in their destiny. The study suggests a qualitative approach and the establishment of a focus group environmental matrix as a one-of-a-kind technique for oil spill control that takes into account people's perspectives. The following objectives help develop a broader understanding of oil exploration and production in local communities, particularly Nigeria, based on established literature, establishing a protocol for engaging with community leaders, managing focus groups, and reporting on the focus groups' findings. This research adopts a qualitative method, based on a focus group discussion of 12 open-ended questions about the effects of the oil spill on the ecology. The focus of the questions was on the impact of the spills on local inhabitants. The qualitative research took place in Ogoniland's Gio, Ogale, Kwawa, and KeDere communities between March and May 2018. With 48 participants and pre-determined questions, gender-based techniques were investigated. Participants were asked leading questions and were native speakers with knowledge of the specified issue. Finally, matrix analysis was performed to match the perspectives of the people, and the results revealed that the overall environmental components were altered. Unsustainable income, devalued economy, devalued culture, weathering mangrove, respiratory problems, inaccuracy in reaction, communication barrier, and economic deterioration are among the repercussions of oil pollution identified by the focus group matrix. The importance of using focus groups to promote environmental restoration and sustainability was determined. It allows for a more direct link with the most vulnerable, as well as potential answers for policymakers.